PENGARUH KENAIKAN HARGA JUAL TERHADAP TOTAL PENJUALAN KACA PADA PT MULTHI ARTHA GRAHA JAKARTA - Windy Gustia Wardani (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
Thespurpose of this studyswas to determine theseffect of increasingsselling pricesson total salessat PT Multi ArthasGraha Jakarta.sThissresearch methodologysuses quantitative researchsmethods, starting fromsthe object ofsresearch atsPT Multi ArthasGraha Jakarta. The methodsthat theswriter uses to write this thesis issthrough librarysresearch and fieldsresearch. To besable to determine theseffect of increasing sellingsprices onstotal salessof PTsMulti ArthasGraha Jakarta, we can use correlationsanalysis as a testing tool. Meanwhile, to find out how big the role of the increase in selling prices insincreasing total sales can be measured by the coefficient of determination or the determining coefficient. This test uses a hypothesis test (t test) with a confidence level of 5% (? = 0.05). Based on the results of the study showed that for six years the company experienced an increase in sales. Sales in 2009 is the base year so there has been no addition or 100.0 and from 2010 to 2014 it was made the current year, in 2010 the index was 110.9, in 2011 it was 123.3, in 2012 it was 136, 6 in 2013 amounted to 151.4 in 2014 amounted to 167.2. Based on the correlation analysis, it is known that the correlation value (r) = 0.99 means that there is a very strong relationship between the increase in selling prices and total sales. While the coefficient of determination is obtained at r2 = 98 and the remaining 1.9% is influenced by other factors that cannot be explained.